INTERPRETASI SABAR DALAM AL-QUR’AN: Studi Komparatif Al-Qurthubi dan Ibnu Katsir - Zabidi, Ahmad; Hamnah, Hamnah; Maulana, Maulana (Borneo : Journal of Islamic Studies, 2023)
When someone experiences adversity or a test from Allah Swt., they frequently use the expression "patience." However, in essence, patience is Allah's way of testing His servants who truly believe in Allah and are sincere in accepting destiny and provisions from Allah so that humans return to the path of Allah and are always patient and try to reflect on every calamity and disaster that comes from Allah Swt. This research is a type of qualitative library research. The data sources are both primary and secondary data originating from library sources. The analysis method uses content analysis to reveal patience in the Al-Qur'an regarding the similarities and differences in terms of interpretation of the two mufassir figures, namely Al-Qurthubi and Ibnu Katsir. So it can be understood that patience is an attitude to restrain oneself from anxiety and emotions, restrain one's words from complaining, and restrain oneself. Al-Qurthubi defines patience as a prohibition against dreaming about everything that God has given him. Meanwhile, according to Ibnu Kathir, patience is someone who is patient in poverty, suffering, and during times of war with all adversities and various kinds of shortcomings.